Epidemiological Investigation in Diphtheria Control in Banda Aceh, Indonesia - Zahratul Aini; Eti Poncorini Pamungkasari; Ari Natalia Probandari (Masters Program in Public Health, 2020)
Background: Extraordinary events (KLB) diph